Students Who Drive the Spirit of Learning through the Actualization of the Teaching Campus Program - Mulya, Valevi Intan Devia; Susilo, Agus (Universitas Muhammadiyah Sidoarjo, 2025)
Educational inequality in Indonesia’s frontier, outermost, and disadvantaged (3T) areas results in low student motivation and limited access to quality education. To address this, the Teaching Campus Program—part of the Merdeka Belajar Kampus Merdeka (MBKM) initiative—deploys university students to assist in under-resourced schools. This study examines how the program enhances student motivation through direct involvement of Teaching Campus participants. Using descriptive qualitative methods, data were collected through observation and documentation to capture real interactions between students and program participants. The findings reveal that university students positively influence learning motivation by applying creative strategies, including digital media, project-based learning, educational games, and positive peer modeling. These approaches helped students act as academic mentors and emotional supporters, increasing confidence and engagement among schoolchildren. The study supports Self-Determination Theory and Social Cognitive Theory by demonstrating how autonomy, competence, relatedness, and self-efficacy can be fostered in rural educational environments through peer-based learning. Practically, the findings inform schools, policymakers, and universities on designing more effective Teaching Campus implementations. Despite its contributions, the study is limited to a single school and lacks comparative data. Further research is needed to evaluate long-term outcomes and apply findings across diverse educational contexts to ensure broader impact. Highlights: Enhances student motivation through creative, engaging teaching methods. Promotes autonomy and self-efficacy aligned with psychological learning theories. Supports practical improvement for 3T schools via university student involvement. Keywords: Educational Inequality, Teaching Campus Program, Student Motivation, Rural Education, Peer-Based Learning